Magnesium-based cementing material and preparation method thereof

By using hydrating agents and carbonating reagents in magnesium-based gelling materials to form a continuous network structure of hydrated magnesium carbonate, the problems of poor mechanical properties and poor carbon sequestration effects in the early stages of magnesium-based adhesive materials are solved, and the density and compressive strength of the material are improved, while reducing carbon emissions.

CN119569404AActive Publication Date: 2025-03-07HUBEI UNIV OF TECH

Patent Information

Application Number
CN202411654113.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-07
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Calcined magnesite as a magnesium-based adhesive material has problems of poor mechanical properties and poor carbon sequestration effect in the early stage.

Method used

By using hydrating agents and carbonating reagents in magnesium-based gelling materials to form a continuous network structure of hydrated magnesium carbonate, filling the voids, achieving carbon sequestration while improving the density and compressive strength of the material.

Benefits of technology

It effectively improves the compressive strength and density of magnesium-based gelling materials, while achieving the effect of carbon sequestration and reducing carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569404A_ABST
    Figure CN119569404A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium-based cementitious material and a preparation method thereof, and relates to the field of magnesium-based cementitious materials, and the magnesium-based cementitious material is prepared from the following components: 80-120 parts of magnesium oxide cement, 0.1-0.6 part of a hydrating agent, 0.6-1.2 parts of a carbonation auxiliary agent, 120-180 parts of aggregate, and 50-60 parts of water. The carbonation auxiliary agent comprises one or more of sodium bicarbonate, sesquicarbonate dihydrate and hydromagnesite seeds. The hydrating agent and the carbonating agent cooperate to form a continuous network structure of hydrated magnesium carbonate in the magnesium-based cementing material to fill gaps, and the density and compressive strength of the magnesium-based cementing material are improved while carbon sequestration is performed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of magnesium-based gelling materials, and in particular to a magnesium-based gelling material and a preparation method thereof. Background Art

[0002] The preparation and production of widely used silicate cement (PC) is accompanied by the consumption of a large amount of calcium raw materials, mainly limestone, and at the same time generates a large amount of energy consumption and releases a large amount of carbon dioxide. In order to reduce carbon emissions, the use of technical routes that replace or partially replace silicate cement is conducive to reducing carbon emissions. At present, calcined magnesite is a new magnesium-based binder material. Its distribution area is less affected by regional factors and its reserves are huge. It is used as a preliminary alternative material for silicate cement. However, the cementitious material prepared by calcined magnesite as a magnesium-based binder material has the problems of poor early mechanical properties and poor carbon fixation effect. Summary of the invention

[0003] In view of the shortcomings of the above-mentioned related technologies, the present application provides a magnesium-based cementitious material and a preparation method thereof. The present application forms a continuous network structure of hydrated magnesium carbonate in the magnesium-based cementitious material by hydrating the agent and carbonating the agent to fill the voids, thereby fixing carbon and improving the density and compressive strength of the magnesium-based cementitious material.

[0004] In the first aspect, the present application provides a magnesium-based gelling material adopting the following technical solution:

[0005] A magnesium-based cementitious material is made of the following components: 80-120 parts of magnesium oxide cement, 0.1-0.6 parts of a hydrating agent, 0.6-1.2 parts of a carbonation aid, 120-180 parts of aggregate, and 50-60 parts of water;

[0006] The carbonation aid includes one or more of sodium bicarbonate, sodium sesquicarbonate dihydrate and hydrogen magnesite seeds.

[0007] Preferably, the carbonation aid comprises hydrogen magnesite seeds and sodium sesquicarbonate dihydrate in a weight ratio of 1:1-1.5.

[0008] Preferably, the carbonation aid comprises hydrogen magnesite seeds and sodium sesquicarbonate dihydrate in a weight ratio of 1:1.24.

[0009] Preferably, the hydrating agent includes one or both of sodium chloride and magnesium acetate.

[0010] Preferably, the hydrating agent is magnesium acetate.

[0011] Preferably, the weight ratio of the water to the magnesium oxide cement is 0.5-0.6:1.

[0012] Preferably, the weight ratio of the water to the magnesium oxide cement is 0.55:1.

[0013] Preferably, the magnesium oxide cement comprises magnesium oxide, silicon dioxide, calcium oxide and iron oxide.

[0014] Preferably, the weight ratio of the magnesium oxide to the silicon dioxide is 9:0.4-0.5.

[0015] Preferably, the weight ratio of the magnesium oxide to the silicon dioxide is 61:3.

[0016] Using the above technical solution, in this application, the hydration and carbonation reactions of magnesium oxide cement are shown in the following formula:

[0017] MgO+H 2 O→Mg(OH) 2 ;

[0018] 2Mg(OH) 2 +CO 2 +2H 2 O→MgCO 3 Mg(OH) 2 ·3H 2 O;

[0019] Mg(OH) 2 +CO 2 +2H 2 O→MgCO 3 ·3H 2 O;

[0020] 5Mg(OH) 2 +4CO 2 →4MgCO 3 Mg(OH) 2 ·4H 2 O;

[0021] 5Mg(OH) 2 +4CO 2 +H 2 O→4MgCO 3 Mg(OH) 2 ·5H 2 O;

[0022] On the one hand, it is beneficial to absorb and utilize carbon dioxide in the matrix of the magnesium-based gel material and the air to fix carbon and reduce carbon emissions. On the other hand, it is beneficial to the formation of hydrated magnesium carbonate and improves the compressive strength of the magnesium-based gel material.

[0023] In the second aspect, the present application provides a method for preparing a magnesium-based gelling material using the following technical solution:

[0024] A method for preparing a magnesium-based cementitious material comprises the following steps: mixing magnesium oxide cement and aggregate to obtain a solid mixture, mixing a hydrating agent, a carbonation aid and water to obtain a liquid mixture, mixing and stirring the solid mixture with the liquid mixture to obtain a solid-liquid mixture, and curing the solid-liquid mixture by controlling the carbon dioxide concentration and relative humidity to obtain the magnesium-based cementitious material.

[0025] Preferably, the curing includes pre-curing for 1-2 days at a temperature of 50-60°C.

[0026] Preferably, the carbon dioxide concentration condition for the maintenance is controlled at 5-20%.

[0027] Preferably, the carbon dioxide concentration condition for the maintenance is controlled to be 10%.

[0028] Preferably, the relative humidity condition of the curing is controlled to be 70-85%.

[0029] Preferably, the relative humidity condition of the curing is controlled to be 78%.

[0030] In summary, the present application includes at least one of the following beneficial technical effects:

[0031] 1. The present invention forms a continuous network structure of hydrated magnesium carbonate in the magnesium-based cementitious material by synergizing the hydrating agent and the carbonating aid to fill the voids, thereby fixing carbon and improving the density and compressive strength of the magnesium-based cementitious material.

[0032] 2. The present application reduces the formation of brucite on the surface of magnesium oxide by selecting a carbonation aid, thereby expanding the reaction surface area, carrying out continuous hydration and carbonation, and further improving the carbonation degree (carbonation degree) and compressive strength.

[0033] 3. The present application controls the carbon dioxide concentration and relative humidity conditions during curing to meet the optimal carbon dioxide concentration for the development of the strength of the solid-liquid mixture while providing the water consumption required for the carbonation reaction. The combined effect is beneficial to the hydration and carbonation reactions, thereby improving the compressive strength of the magnesium-based cementitious material. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a thermogravimetric analysis diagram of Example 2 of the present application;

[0035] Figure 2 is a thermogravimetric analysis diagram of Example 6 of the present application;

[0036] Figure 3 is a thermogravimetric analysis diagram of Example 7 of the present application;

[0037] Figure 4This is the thermogravimetric analysis diagram of Comparative Example 1 of the present application;

[0038] Figure 5 This is the thermogravimetric analysis diagram of comparative example 3 of the present application. DETAILED DESCRIPTION

[0039] The present application is further described in detail below in conjunction with examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to normal conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present invention.

[0040] The raw materials used in the examples and comparative examples can be obtained from commercial sources. The content of each component in magnesium oxide cement is as follows: MgO content 91.5%, SiO 2 Content 4.5%, CaO content 2.5%, Fe 2 O 3 Content 1%.

[0041] Examples 1-7

[0042] Examples 1-7 of the present application provide a magnesium-based gelling material, the preparation steps of which are as follows:

[0043] The magnesium oxide cement and aggregate are mixed to obtain a solid mixture, a hydrating agent, a carbonation aid and water are mixed to obtain a liquid mixture, the solid mixture and the liquid mixture are mixed and stirred to obtain a solid-liquid mixture, the carbon dioxide concentration is controlled to be 10% and the relative humidity is controlled to be 78%, the solid-liquid mixture is pre-cured at a temperature of 50-60° C. for 1 day, and then cured at room temperature to obtain a magnesium-based cementitious material.

[0044] The composition and proportion of the raw materials of Examples 1-7 are shown in Table 1 below:

[0045] Table 1:

[0046]

[0047] Example 8

[0048] Example 8 of the present application provides a magnesium-based cementitious material. The difference between Example 8 and Example 2 is that the carbon dioxide concentration condition for curing and controlling the magnesium-based cementitious material in Example 8 during the preparation process is 5%.

[0049] Example 9

[0050] Example 9 of the present application provides a magnesium-based cementitious material. The difference between Example 9 and Example 2 is that the carbon dioxide concentration condition for curing and controlling the magnesium-based cementitious material in Example 9 during the preparation process is 20%.

[0051] Example 10

[0052] Example 10 of the present application provides a magnesium-based cementitious material. The difference between Example 10 and Example 2 is that the relative humidity condition of the magnesium-based cementitious material of Example 10 during the preparation process is maintained and controlled at 70%.

[0053] Embodiment 11

[0054] Example 11 of the present application provides a magnesium-based cementitious material. The difference between Example 11 and Example 2 is that the relative humidity condition of the magnesium-based cementitious material of Example 11 during the preparation process is maintained and controlled at 85%.

[0055] Comparative Example 1

[0056] Comparative Example 1 provides a magnesium-based gelling material. The difference between Comparative Example 1 and Example 2 is that Comparative Example 1 uses 0.29 g of sodium carbonate instead of sodium bicarbonate as a carbonation aid.

[0057] Comparative Example 2

[0058] Comparative Example 2 provides a magnesium-based gelling material. The difference between Comparative Example 2 and Example 2 is that during the preparation process of Comparative Example 2, 0.26 g of magnesium chloride is used instead of magnesium acetate as a hydrating agent.

[0059] Comparative Example 3

[0060] Comparative Example 3 provides a magnesium-based gelling material. The difference between Comparative Example 3 and Example 2 is that no hydrating agent is added during the preparation process of Comparative Example 3.

[0061] Test and Inspection

[0062] (1) Testing the 14d compressive strength of the magnesium-based cementitious materials of Examples 1-11 and Comparative Examples 1-3,

[0063] The 28d compressive strength is shown in Table 2 below.

[0064] (2) The magnesium-based gelling materials of Examples 1-11 and Comparative Examples 1-3 were subjected to thermogravimetric analysis on a TGA-4000 device under the following conditions: temperature range 30-950°C, nitrogen atmosphere, heating rate 10°C / min. CO 2 The solid-to-storage ratio is shown in Table 2. The thermogravimetric analysis diagrams of Example 2, Example 6, Example 7, Comparative Example 1 and Comparative Example 3 are shown in Table 2. Figure 1-5 shown.

[0065] CO 2 Sequestration ratio (S CO2 ) is calculated as shown in the formula: S CO2 =P CO2 / P RMC In the formula, P CO2 To store CO 2 The percentage of mass loss caused by decarburization is P RMC is the percentage of MgO (i.e. the mass percentage of residual MgO after heating to 950°C).

[0066] Table 2:

[0067] Data Source <![CDATA[CO 2 Solid storage ratio (%)]]> 14d compressive strength (MPa) 28d compressive strength (MPa) Example 1 25.30 30 33 Example 2 28.84 35 38 Example 3 26.47 33 36 Example 4 23.63 24 28 Example 5 32.22 53 57 Example 6 36.11 47 49 Example 7 43.79 66 68 Example 8 27.13 30 37 Example 9 26.03 21 35 Example 10 25.31 30 34 Embodiment 11 27.34 33 36 Comparative Example 1 17.89 15 21 Comparative Example 2 18.14 16 20 Comparative Example 3 15.12 11 15

[0068] Results Analysis

[0069] According to Table 1-2 and Figure 1-5 The data and graphs provided are further analyzed for this application.

[0070] Reference Figure 1-5 The thermal decomposition process of magnesium-based cementitious materials is divided into three stages. The first stage is the dehydration of bound water in magnesium-based cementitious materials below 300°C, the second stage is the decomposition of uncarbonized brucite at 300-460°C, and the third stage is the dehydroxylation and decarbonization of magnesium-based cementitious materials at 460-900°C. The deconvolution of the weight loss curve is used to distinguish different decomposition stages, and the area corresponding to each phase decomposition is obtained to calculate the CO 2 Sequestration ratio, CO 2 The higher the solid storage ratio, the higher the carbonization degree (carbonation degree) of the magnesium-based cementitious material. 2 The CO sequestration ratio is higher than that of the comparative examples 1-3. 2 The solid-storage ratio indicates that the carbonation degree of the magnesium-based cementitious materials of Examples 1-11 of the present application is higher than that of the comparative examples 1-3, and the 14d compressive strength and 28d compressive strength of the magnesium-based cementitious materials of Examples 1-11 of the present application are much higher than those of the comparative examples 1-3.

[0071] Taking Example 2 as a reference, Examples 1 and 3 show the effect of the ratio of water to magnesium oxide cement on the carbonation degree and compressive strength of magnesium-based cementitious materials, wherein the carbonation degree and compressive strength of magnesium-based cementitious materials in Example 2 are 2 The solid storage ratio, 14d compressive strength and 28d compressive strength of the magnesium-based cementitious materials of Example 1 and Example 3 are all higher than CO 2 The solid-storage ratio, 14d compressive strength and 28d compressive strength indicate that controlling the water-cement ratio to 0.55 is beneficial to improving the CO 2Solid-storage ratio, 14d compressive strength and 28d compressive strength.

[0072] Taking Example 2 as a reference, Example 4 shows the effect of the type of hydrating agent on the carbonation degree and compressive strength of the magnesium-based cementitious material. 2 The solid storage ratio, 14d compressive strength and 28d compressive strength are all higher than those of the magnesium-based cementitious material in Example 2. 2 The solid-storage ratio, 14d compressive strength and 28d compressive strength indicate that the use of magnesium acetate as a hydrating agent is beneficial to improving the CO 2 Solid-storage ratio, 14d compressive strength and 28d compressive strength.

[0073] Taking Example 2 as a reference, Examples 5-7 show the effects of the types and proportions of carbonating agents on the carbonation degree and compressive strength of magnesium-based cementitious materials. 2 The solid storage ratio, 14d compressive strength and 28d compressive strength are all higher than those of the magnesium-based cementitious material in Example 2. 2 The solid-storage ratio, 14d compressive strength and 28d compressive strength indicate that the use of sodium sesquicarbonate dihydrate as a carbonating agent is more beneficial to improving the CO content of magnesium-based cementitious materials than that of sodium bicarbonate as a carbonating agent. 2 Solid-storage ratio, 14d compressive strength and 28d compressive strength. On the other hand, it can be seen from Examples 6 and 7 that after adding hydrogen magnesite seeds, the CO 2 The improvement of solid storage ratio, 14d compressive strength and 28d compressive strength is much higher than that of Example 6 compared with Example 5. 2 The increases in solid-storage ratio, 14d compressive strength and 28d compressive strength indicate that the use of sodium sesquicarbonate dihydrate and hydrogen magnesite seeds as carbonation agents is effective in improving the CO2 content of magnesium-based cementitious materials. 2 There is a synergistic effect in terms of solid-storage ratio, 14d compressive strength and 28d compressive strength.

[0074] Taking Example 2 as a reference, Examples 8-11 demonstrate the effects of carbon dioxide concentration and relative humidity on the carbonation degree and compressive strength of magnesium-based cementitious materials during the curing process, wherein the CO2 solidification ratio, 14d compressive strength and 28d compressive strength of the magnesium-based cementitious materials of Example 2 are all higher than those of the magnesium-based cementitious materials of Examples 8-11, indicating that controlling the carbon dioxide concentration condition to 10% is beneficial to improving the CO2 solidification ratio, 14d compressive strength and 28d compressive strength of the magnesium-based cementitious materials, and controlling the relative humidity condition to 78% is beneficial to improving the CO2 solidification ratio, 14d compressive strength and 28d compressive strength of the magnesium-based cementitious materials.

[0075] Taking Example 2 as a reference, the CO2 solid storage ratio, 14d compressive strength and 28d compressive strength of the magnesium-based cementitious material obtained by using sodium carbonate as the carbonating agent instead of sodium bicarbonate in Comparative Example 1 are much lower than the CO2 solid storage ratio, 14d compressive strength and 28d compressive strength of the magnesium-based cementitious material in Example 2, indicating that the use of sodium bicarbonate and sodium sesquicarbonate dihydrate as the carbonating agent is beneficial to greatly improve the carbonation degree and compressive strength of the magnesium-based cementitious material. Comparative Examples 2 and 3 show the influence of whether to add a hydrating agent and the type of hydrating agent on the carbonation degree and compressive strength of magnesium-based cementitious materials. In Comparative Example 2, the CO2 solid storage ratio, 14d compressive strength and 28d compressive strength of the magnesium-based cementitious material obtained by using magnesium chloride as a hydrating agent to replace magnesium acetate are much lower than the CO2 solid storage ratio, 14d compressive strength and 28d compressive strength of the magnesium-based cementitious material in Example 2. In Comparative Example 3, the CO2 solid storage ratio, 14d compressive strength and 28d compressive strength of the magnesium-based cementitious material obtained without using a hydrating agent are further reduced on the basis of Comparative Example 2, indicating that the use of magnesium acetate and sodium chloride as hydrating agents is beneficial to significantly improve the carbonation degree and compressive strength of the magnesium-based cementitious material.

[0076] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A magnesium-based gelling material, characterized in that: It is made of the following components: 80-120 of magnesium oxide cement, 0.1-0.6 of hydrating agent, 0.6-1.2 of carbonation aid, 120-180 of aggregate, and 50-60 of water; The carbonation aid includes one or more of sodium bicarbonate, sodium sesquicarbonate dihydrate and hydrogen magnesite seeds.

2. A magnesium-based gelling material according to claim 1, characterized in that: The carbonation aid comprises hydrogen magnesite seeds and sodium sesquicarbonate dihydrate in a weight ratio of 1:1-1.

5.

3. A magnesium-based gelling material according to claim 1, characterized in that: The hydrating agent includes one or both of sodium chloride and magnesium acetate.

4. The magnesium-based gelling material according to claim 1, characterized in that: The weight ratio of the water to the magnesium oxide cement is 0.5-0.6:

1.

5. The magnesium-based gelling material according to claim 1, characterized in that: The magnesium oxide cement comprises magnesium oxide, silicon dioxide, calcium oxide and iron oxide.

6. A magnesium-based gelling material according to claim 5, characterized in that: The weight ratio of the magnesium oxide to the silicon dioxide is 9:4-5.

7. A method for preparing a magnesium-based gelling material as claimed in claims 1 to 6, characterized in that: The method comprises the following steps: mixing magnesium oxide cement and aggregate to obtain a solid mixture, mixing a hydrating agent, a carbonation aid and water to obtain a liquid mixture, mixing and stirring the solid mixture and the liquid mixture to obtain a solid-liquid mixture, and curing the solid-liquid mixture by controlling the carbon dioxide concentration and relative humidity to obtain the magnesium-based cementitious material.

8. The method for preparing a magnesium-based gelling material according to claim 7, characterized in that: The curing includes pre-curing for 1-2 days at a temperature of 50-60°C.

9. The method for preparing a magnesium-based gelling material according to claim 7, characterized in that: The carbon dioxide concentration condition for the maintenance is controlled to be 5-20%.

10. The method for preparing a magnesium-based gelling material according to claim 7, characterized in that: The relative humidity condition of the curing is controlled at 70-85%.

Citation Information

Patent Citations

  • Magnesium-based cementing material as well as preparation method and application thereof

    CN113896442A

  • Method for preparing cementitious material composition, cementitious material and application of cementitious material

    CN115073032A

  • Green cementing material capable of realizing carbon reduction and carbon sequestration effects and preparation method of green cementing material

    CN116102272A

  • Reactive magnesium oxide cements

    CN1419523A

  • Magnesium-based cementitious material, preparation method and application thereof

    US20230159389A1

Cited By

  • Magnesium oxide-based building material based on complete cyclic utilization of seawater desalination brine resources as well as preparation method and application of magnesium oxide-based building material

    CN120923201A